Synthesis of Long Oxahelicenes by Polycyclization in a Flow Reactor. (13th April 2017) - Nejedlý, Jindřich; Šámal, Michal; Rybáček, Jiří; Tobrmanová, Miroslava; Szydlo, Florence; Coudret, Christophe; Neumeier, Maria; Vacek, Jaroslav; Vacek Chocholoušová, Jana; Buděšínský, Miloš; Šaman, David; Bednárová, Lucie; et al.
Abstract: A series of oxahelicenes composed of ortho / meta ‐annulated benzene/pyridine and 2 H ‐pyran rings were synthesized on the basis of the cobalt(I)‐mediated (or rhodium(I)‐ or nickel(0)‐mediated) double, triple, or quadruple [2+2+2] cycloisomerization of branched aromatic hexa‐, nona‐, or dodecaynes, thus allowing the construction of 6, 9, or 12 rings in a single operation. The use of a flow reactor was found to be beneficial for the multicyclization reactions. The stereogenic centers present in some of the oligoynes steered the helical folding in such a way that the final oxa[9]‐, [13]‐, [17]‐ and [19]helicenes were obtained in both enantiomerically and diastereomerically pure form. Specifically, the oxa[19]helicenes beat the current record in the length of a helicene backbone. Single‐molecule conductivity was studied by the mechanically controllable break‐junction method with a pyridooxa[9]helicene.